Neuropsychiatric Symptoms in Behavioral Variant Frontotemporal Dementia and Alzheimer's Disease: A 12-Month Follow-Up Study - Da Silva, Thais Bento Lima; Ordonez, Tiago Nascimento; Bregola, Allan Gustavo; Bahia, Valéria Santoro; Cecchini, Mário Amore; Guimarães, Henrique Cerqueira; Gambogi, Leandro Boson; Caramelli, Paulo; Balthazar, Marcio Luiz Figueredo; Damasceno, Benito Pereira; Brucki, Sonia Maria Dozzi; de Souza, Leonardo Cruz; et al. (Frontiers in Neurology, 2021)
Introduction. Neuropsychiatric symptoms in patients with frontotemporal dementia (FTD) are highly prevalent and may complicate clinical managements. Objective: We tested whether the Neuropsychiatry Inventory (NPI) could detect change in neuropsychiatric symptoms and caregiver´s distress in patients diagnosed with behavioral variant frontotemporal dementia (bvFTD) and Alzheimer's disease (AD) from baseline to a 12-month follow-up. Methods: The sample consisted of 31 patients diagnosed with bvFTD and 28 patients with AD and their caregivers. A sociodemographic questionnaire, the Mini-Mental State Examination (MMSE), Addenbrooke´s Cognitive Examination Revised (ACE-R), the INECO Frontal Screening (IFS), the Frontal Assessment Battery (FAB), the Executive Interview (EXIT-25) and the Neuropsychiatric Inventory (NPI) were used. Descriptive statistics, Mann-Whitney U test, Wilcoxon test, χ2 test and Linear Regression Analysis were used. Results: Neuropsychiatric symptoms total (NPI Total) and the caregiver Distress score were statistically higher among bvFTD patients at both assessment points. MMSE, ACE-R scores significantly declined and NPI Total and Distress scores significantly increased in both groups. Age was the only independent predictor variable for the NPI Total score in the bvFTD group in the follow up. In the AD group, ACE-R and EXIT-25, conjunctively, were associated with the NPI total score at follow up. Conclusions: Knowing how symptoms evolve over the course of the disease could help the clinician and the caregiver in decisions regarding future management and therapeutic approaches.